Financial Integration and Risk-Adjusted Growth Opportunities - Ivaschenko, Iryna (IMF Working Papers; Working Paper ;, 2008)
This paper documents the evolution of measures of financial integration for major advanced and emerging markets economies, assesses whether advances in integration have had a significant positive impact on countries' risk-adjusted growth opportunities, and identifies some of the channels through which financial integration may foster growth. Three main results obtain. First, financial integration has progressed significantly worldwide, particularly in emerging markets, and regional integration has advanced at the fastest pace in Europe. Second, a country's speed of integration predicts future country's risk-adjusted growth opportunities, while improved risk-adjusted growth opportunities predict future advances in integration, indicating that the countries whose integration has been faster may have benefited most from a virtuous dynamics in which financial integration and improved real prospects are mutually reinforcing. Third, financial integration predicts globalization but the reverse does not necessarily hold, while advances in financial integration predict advances in financial development and improvements in the liquidity of equity markets.